Impact of Economic Growth on Bank Liquidity: A Case of Nepal - Bhatta, Kamala Kumari; Pokhrel, Lelina; Subedi, Gaurav; Kunwar, Kushal; Sah, Laxmi Kumari (Nepalese Journal of Business, 2025)
The study examines the impact of economic growth on bank liquidity in the contex of Nepal. Return on assets and cash reserve ratio are selected as the dependent variables. The selected independent variables are GDP growth rate, money supply, bank rate, inflation, remittance, and per capita income. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2013/14 to 2022/23. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB), annual reports of the selected commercial banks, World Bank and OECD Inflation CPI indicator. The correlation coefficients and regression models are estimated to test the significance and importance of economic growth on bank liquidity: A case of Nepal. The study showed that GDP growth rate has a positive impact on return on assets and cash reserve ratio. It indicates that higher the GDP growth rate, higher would be the return on assets and cash reserve ratio. Similarly, money supply has a positive impact on return on assets and cash reserve ratio. It indicates that higher the money supply, higher would be the return on assets and cash reserve ratio. Likewise, remittance has a positive impact on return on assets and cash reserve ratio. It indicates that higher the remittance, higher would be the return on assets and cash reserve ratio. Further, per capita income has a positive impact on return on assets and cash reserve ratio. It indicates that higher the per capita income, higher would be the return on assets and cash reserve ratio. However, inflation has a negative impact on return on assets and cash reserve ratio. It indicates that increase in inflation leads to decrease in return on assets and cash reserve ratio. Likewise, bank rate has a negative impact on return on assets and cash reserve ratio. It indicates that higher the bank rate, lower would be the return on assets and cash reserve ratio.